ANSWER
B. x=3,y=2
Step-by-step explanation
The given equations are
![x - 3y = - 3...(1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fkvm29vfi95c24m91bod08prcnny03i4fe.png)
and
![x + 3y = 9...(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/6c0pxkrhzdnh900xihrro02c5g2k75xhxm.png)
We add the two equations to eliminate y.
This implies that that:
![x + x - 3y + 3y = 9 + - 3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ajbflqkpnmveyym4c69cx13tbsln7nbznm.png)
Simplify:
![2x = 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/90ubaxo95rs22p9vo1ughaaubcptocrlpc.png)
Divide both sides by 2.
![x = 3](https://img.qammunity.org/2020/formulas/mathematics/high-school/gn0ewdpib9ooyfthsjwp8oi4900vxj88n6.png)
We put x=3 into any of the equations to find y.
Let us substitute x=3 into equation (1) to get:
![3 - 3y = - 3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tpu6c3hw9pk7tuwjh3572fnpxmvh9ceoet.png)
![- 3y = - 3 - 3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/k03im1g19i0qcewcj2mh2btdjgfl7wozlg.png)
![- 3y = - 6](https://img.qammunity.org/2020/formulas/mathematics/middle-school/v0ivu3lu8lfhhnrun1rlpnahettpx6ss3l.png)
Divide both sides by -3 to get;
![y = 2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5y42wc6ogpkf35oxmmrrzcklsqb9b714mu.png)
The solution is therefore x=,y=2.